Here's the question you clicked on:
MaryJSmith
3x=4x-6
Move x to one side. And solve.
3x - 4x = 4x - 6 - 4x Now solve for x =)
I just got so confused...
So we're solving for x. In order to solve for x we have to leave x by itself on one side. From 3x = 4x - 6 we can subtract 4x from both side to leave x by itself on the left side and a numerical value on the right side. You'll end up with -x = -6. Now this is -x but we want x. So we multiply both side by -1 to get a x. Negative times negative equals positive. (-x)(-1) = (-6)(-1) We will end up with: x = 6
Oh I get it , thank you : )